Clinical Case Therapeutic consultation a patient with damage to the oral mucosa from the dentist. When, why, about what? - Elena A. Temnikova; Anna V. Chekina; Kira V. Vetkova (LLC "MEDIAFORMAT", 2024)
Oral mucosal pathology is a significant problem in stomatology due to the complexity of a differential diagnosis and often requires the systemic therapy of it. Therefore, it is not uncommon for patients with diseases of the oral mucosa to be referred to a therapeutic physician to find the etiological factor of oral mucosa disease and to choose the systemic therapy. However, the purpose of the consultation and the capacity of the therapist's physician in such situations may be interpreted differently by stomatologists and therapists. There is an example of the patient with lichen planus. The main tasks of the therapist consultation in this case are: to provide a general clinical examination of the possible somatic manifestations of the lichen planus autoimmune process, to evaluate the therapy to exclude possible influence some of the medication to the lesion of oral mucosal or progression lichen planus, to assess the general condition of the patient in order to select the treatment regimens using systemic corticosteroids and risk factors for the development of side effects of this therapy.